2020
DOI: 10.1177/2150132720942705
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Challenges to Health Care Delivery Faced by Cancer Patients in India During the COVID-19 Pandemic

Abstract: Introduction Access to health care and care delivery during the COVID-19 pandemic may be challenging for cancer patients. Several guidelines have been developed, which recommend treatment adjustments depending on the site of cancer, grade, and stage. However, few studies in India and across the globe have looked into the real challenges faced by cancer patients and assessed the effectiveness of the adopted interventions. This study was undertaken with the objective to study the challenges faced by cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 23 publications
1
69
0
Order By: Relevance
“…(II) Experiences of accessing cancer treatment and care services Participants in the majority of the included studies reported experiences of treatment delays [17,18,20,22,24,[25][26][27][28][29][30][31].…”
Section: Results Of Thematic Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…(II) Experiences of accessing cancer treatment and care services Participants in the majority of the included studies reported experiences of treatment delays [17,18,20,22,24,[25][26][27][28][29][30][31].…”
Section: Results Of Thematic Synthesismentioning
confidence: 99%
“…Reasons ranged from hospital cancellations, city lockdowns and swabbing requirements. Deferral of radiotherapy dates and long waiting hours beyond scheduled appointment times was a problem cited by a number of participants in one study conducted in India [30]. Another study conducted in Italy reported that radiation, infusion therapies and surgical tumour removal experienced the most disruption [31].…”
Section: Results Of Thematic Synthesismentioning
confidence: 99%
See 3 more Smart Citations